A double-loop process for beach quality index construction: Approaching the complexity of the Catalan coast. (15th June 2019) - Bombana, Briana; Ariza, Eduard
Abstract: Sets of coastal management indicators have been used to summarize the main social, economic, environmental and political assets/processes of socio-ecological systems (SES). Their development and further assessment have, usually, been ruled by a process of four sequential steps (Selection/definition of indicators, Production, Assessment and Information for policy actions), in which feedback is limited to certain subjects and attributes. Quality checks regarding the information made available are rarely seen, somewhat disregarding the adaptive complex character of SES. In this study, we present the double-loop (DL) process of learning, aiming at improving the epistemological (usefulness) and pragmatic (pertinence) quality of knowledge. In practice, an expanded peer assessment has led to the adjustment of a previous beach management tool: The Beach Quality Index (hereinafter, the single-looped BQI), through the (re)selection, (re)definition and (re)production of indicators. By means of one multi-stakeholder meeting, five focus groups and interviews, four relevant narratives of the Catalan coast were identified. These narratives enabled the shaping of a wider perception of the observed system - the Catalan beaches - which highlighted the lack of integration in beach management processes. In order to respond to the aforesaid lack of integration and other shortcomings, by adding or updating the single-looped BQI indicators, a new formal system and the choices made were formulated and highlighted. This new set of indicators is here called the double-looped BQI, in which, especially, the previous preponderance of recreational activity was counterbalanced. Though further developments would still be necessary and in situ applications would help to check the feasibility of the logic applied, we recommend its inclusion in the beach quality research field to couple better with coastal management recommendations regarding governance and complexity. Highlights: A double-loop (DL) process of learning is presented to renew beach management tools. The embedded expanded peer assessment potentially boosts pertinence and usefulness. A double-looped beach quality index (DL-BQI) included the Catalan coast narratives. Pre-analytical choices were highlighted and focus on recreation was better balanced.